2013
DOI: 10.1038/gim.2012.114
|View full text |Cite
|
Sign up to set email alerts
|

An empirical estimate of carrier frequencies for 400+ causal Mendelian variants: results from an ethnically diverse clinical sample of 23,453 individuals

Abstract: Purpose:Recent developments in genomics have led to expanded carrier screening panels capable of assessing hundreds of causal mutations for genetic disease. This new technology enables simultaneous measurement of carrier frequencies for many diseases. As the resultant rank-ordering of carrier frequencies impacts the design and prioritization of screening programs, the accuracy of this ranking is a public health concern.Methods:A total of 23,453 individuals from many obstetric, genetics, and infertility clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
256
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(269 citation statements)
references
References 24 publications
6
256
3
4
Order By: Relevance
“…Much data on the carrier frequency were already available for many of the diseases frequent among the Ashkenazi Jews. 10,[12][13][14] For diseases that are relatively frequent in the other non-Ashkenazi communities, however, this report is the first to outline carrier frequency based on relatively large numbers of screened individuals. In the few instances where the carrier frequency was lower than expected ( Table 1), it was still more than the 1% frequency recommended for screening by the American College of Medical Genetics and Genomics.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Much data on the carrier frequency were already available for many of the diseases frequent among the Ashkenazi Jews. 10,[12][13][14] For diseases that are relatively frequent in the other non-Ashkenazi communities, however, this report is the first to outline carrier frequency based on relatively large numbers of screened individuals. In the few instances where the carrier frequency was lower than expected ( Table 1), it was still more than the 1% frequency recommended for screening by the American College of Medical Genetics and Genomics.…”
Section: Discussionmentioning
confidence: 86%
“…Such an approach has been proposed by several groups and is beginning to be implemented. 10 One problem is that in a sequential screening program such as the one currently implemented in Israel, a universal test will increase the cases in which one individual is found to be a carrier whereas the other partner is from a community in which the disease is rare. This will invariably increase the couple's level of anxiety and lead to additional tests (e.g., sequencing) that are not justified.…”
Section: Discussionmentioning
confidence: 99%
“…Carrier screening was performed with four targeted mutation panels: the ACMG-recommended core panel with 23 mutations, 7 the Integrated Genetics CFplus panel with 92 CFTR mutations, 9 the Counsyl Family Prep Screen 1.0 panel with 103 CFTR mutations, 8 and the Recombine CarrierMap panel with 108 CFTR mutations (http://www.recombine.com, accessed on 20 January 2015). In addition, mock screening was performed with the hypothetical targeted mutation panel representing the 159 variants characterized by Sosnay et al 11 in genomes from the CFTR2 patient cohort.…”
Section: Cystic Fibrosis Mutation Screening Panelsmentioning
confidence: 99%
“…7 Since the establishment of the core ACMG panel, numerous commercial laboratories have produced expanded genetic panels of 90 or more CFTR variants, including those designed by the genetic testing companies Integrated Genetics, Counsyl, and Recombine. 8,9 Original research article Although DNA genotyping can be extraordinarily accurate from an analytical perspective, it is not sufficient by itself for determination of downstream effects of gene function and prediction of phenotypes in hypothesized homozygous or compound heterozygous individuals (see Cooper et al for a review 10 ). This is especially true for diseases with continuous phenotypes, like CF.…”
Section: Introductionmentioning
confidence: 99%
“…Lazarin et al reported on a targeted mutation panel which analyzed 417 disease causing mutations associated with 108 disorders 20. In their cohort of 23, 453 patients of mixed ethnicities, 24% were identified as carriers of at least one mutation.…”
Section: Expanded Carrier Screeningmentioning
confidence: 99%